Low-Threshold 4/5 Octave-Spanning Mid-Infrared Frequency Comb in a LiNbO $_3$ Microresonator - Weichen Fan; Zhizhou Lu; Wei Li; Xinyu Wang; Mengyao Zhou; Weiqiang Wang; Qibing Sun; Guoxi Wang; Dong Cheng; Leiran Wang; Wenfu Zhang; Wei Zhao (IEEE Photonics Journal)
Mid-infrared (MIR) optical frequency combs (OFCs) are ideal light sources for precision metrology and can find extensive applications, especially in molecular spectroscopy and gas detection. Here the generation of mode-locked MIR frequency comb in a LiNbO $_3$ microring through optimized slot-waveguide design is proposed. Such microcomb can span over four-fifths of an octave (ranging from $\sim$ 2810 nm to $\sim$ 4630 nm) with pump power as low as 50 mW, which can be applied to the 2f-3f self-referencing for fully stabilization and helpful to monolithic integration of the whole system. Further investigations on complex dynamical processes for the microcomb generation suggest that the intracavity soliton drifting caused by the third-order dispersion could be compensated by the self-steepening effect as introducing an additional drift through proper dispersion tailoring. This work could facilitate the low-threshold broadband MIR frequency comb generation technique, as well as provide a way to realize more delicate control of soliton microcombs in both temporal and spectral domain.